The Relationship between Smoking and Coffee Drinking Habits with Hypertension in Internal Medicine Polyclinic Patients at Malingping Hospital Banten - Galuh Nata Kusuma; Annisaa Fitrah Umara; Andi Sudrajat; Karina Megasari Winahyu (Journal of Health Science and Nursing Study, 2022)
Background: Hypertension is a disease that is often found in the community and its prevalence continues to increase. One of the modifiable factors related to hypertension is smoking and dietary consumption. This study aimed to identify the relationships between smoking and drinking coffee with the incidence of hypertension in Internal Medicine Polyclinic patients at Malingping Hospital. Methods: The study used is cross-sectional. Data was collected by measuring blood pressure and questionnaires. A sample of 52 respondents was taken by accidental sampling and analyzed using chi-square. Results: The study showed that there was a significant relationship between smoking and hypertension P-value = 0.021 and coffee drinking habits with hypertension P value = 0.001. Conclusion: Hospitals or health workers are expected to provide counselling in the form of health education about managing smoking habits and coffee consumption in an effort to prevent hypertension in the community. Keywords: hypertension, smoking, drinking coffee